Капитан Наполеон - Лепеллетье Эдмон Адольф (Избранные произведения для юношества, 1992)
Экземпляры: ф.22 (2002) / Инвентарный номер: 43835 / Цена: / Сис.шифр: 84(4Фра)-4 / Авт.знак: Л 48 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-442